First Record of the Little Gulper Shark, Centrophorus uyato (Rafinesque, 1810), in the Turkish Marine Waters of the North Aegean Sea - Ece Yalçın; Kağan Kocakale; Yunus Gönül; Nur Bikem Kesici; Onur Gönülal; Cem Dalyan (Turkish Journal of Bioscience and Collections)
Objective: Gulper sharks, are small to medium-sized benthopelagic deep-water sharks that occur worldwide along the outer continental shelves and upper continental and insular slopes. Centrophorus uyato (Rafinesque, 1810) is a rare species that has only been recorded twice in Turkish marine waters. Our study provides the first record of the species in the Turkish waters of the North Aegean Sea and the third record from the Turkish waters. Materials and Methods: In April 2019, the male specimen of C. uyato was caught at 401 m with trawl commercial fish vessels. The little gulper shark, C. uyato was collected off the Gökçeada coasts, North Aegean Sea. Measurements of the caught specimen are provided and the geographical distribution of the C. uyato in the Mediterranean Sea is documented. Results: The male specimen of C. uyato was caught off the coasts of Gökçeada. It was measured as 775 mm in total length and weighed 3040 g in total weight. Conclusion: In the Turkish marine waters of the Mediterranean Sea, data on the species is lacking because it is hard to find the genus. Their K-selected life strategy makes them vulnerable, so in the Mediterranean region, they have a declining trend. Therefore, identifying the species across its distribution range is an important step for future conservation efforts.